Taxonomic importance of anticlinal walls and stomata patterning in some Melastoma l. Species from Fraser Hill - Zakaria, Siti Maisarah; Che Amri, Che Nurul Aini; Shahari, Rozilawati; Mohd Yunus, Noor Syaheera (Zibeline International, 2020)
The epidermal characteristics of five selected Melastoma L. species in Fraser Hill, Pahang that belongs to Melastomataceae family had been investigated. These five species namely M. muticum Ridl., M. decemfidum Roxb., M. perakense Ridl., M. sanguineum x malabathricum and M. malabathricum var. normale. The objective of this study is to determine whether epidermal characteristics in Melastoma could be taxonomic value in systematic and diagnostic investigations. Methods of the investigation involved epidermal peel and scanning electron microscopy. Results obtained revealed that the presence of hypostomatic stomata and guard cells pairs were elliptic in shaped for all species studied. Apart, the pattern of anticlinal walls on adaxial and abaxial surfaces was straight to wavy for all species studied except for wavy to sinuous anticlinal walls on abaxial surface of M. sanguineum x malabathricum. Furthermore, two types of stomata were observed among species studied such as anomocytic and diacytic stomata. Results showed that diacytic type was only present in M. sanguineum x malabathricum therefore could be a criterion to diagnose the species. Lastly, this present study was also reported on the presence of two types of guard cell pairs such as raised or slightly raised and sunken guard cell pairs. In conclusion, the present study revealed that the anticlinal walls and stomata patterning possess as taxonomic importance in identification and classification of Melastoma either at genus or species level.